On bifurcation points of strongly condensing operators - N. A. Erzakova (Научный вестник МГТУ ГА, 2016)
Two conditions equivalent to complete continuity of Frechet derivative at a point and the asymptotic derivative in the case of their existence are given. Theorem of M.A. Krasnosel’skii on asymptotic bifurcation points for completely con-tinuous fields to class of strongly - condensing at infinity vector fields is generalized.